Prof. Wlodzimierz Nykiel 70: From Cooperation to Friendship - Hamaekers, Hubert (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The article describes the early days and the founding of the Centre for Tax Documentation and Studies by the University of Lodz and the International Bureau of Fiscal Documentation in the nineties and its development in later years. In particular due to its director Prof. Nykiel and its able and dedicated staff the Centre has become a leading tax research and training institute in Central Europe. Courses not only include programmes for master students but also for tax administrators and practitioners from various countries. Special attention goes to international and European tax topics, including the important topic of transfer pricing.